Diseño y construcción de una máquina para realizar cortes de alimentos en formas variadas con capacidad de 20Kg/h, con dosificación controlada destinada a la industria alimenticia - Caiza, Danilo Sebastián (2016)
The design and building of the present project are focused in optimizing the time and guarantee the fulfillment of the company's needs to which the service will be offered to. Nowadays we can observe in small and medium size companies dedicated to the process and cutting of food, the need to apply new technology in machinery dedicated to better the cutting process, so we may optimize the time and consequently generating better production and in less amount of time. The following project begins with the theoretical framework which describes the main concepts of the elements in a food cutting machine for small and medium sized companies. Using the comparative study was selected the best alternative which fulfills with the requirements set for the type of job to be done by the food cutting machine. Once analyzed the criteria and shaving selected the materials to be used, we proceed with the structure calculations and a study of the main parts of the machine all in function to the machines performance and the stress it will go through in its normal functions. Finally, the diagnosis of blueprints are generated, necessary simulations to validate the right functioning of the machine's main components and some conclusions are exposed to confirm the given problem. Keywords: Technical project, design and construction, cut of food, food industry, food in various forms.